Sistem Informasi Pengelolaan Data Service Dan Sparepart Berbasis Multiuser Pada HSC Computer Kaliwungu - Haris Ihsanil Huda; Nuris Dwi Setiawan; Priyadi Priyadi (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to design an information system that can handle the problems that exist in HSC Computer Kaliwungu, in terms of using Information Systems, HSC Computer Kaliwungu still uses manual or conventional systems, namely service data is still stored in books so that the administration has difficulty in making reports, because every month the administration has to recap the service data, to find out the status of service handling the administration has to look in the service book and visit the technician directly, so the information given to customers is not fast. To support the research conducted, the researchers used a Research and Development (R&D) development method approach through the stages of developing a multiuser-based service and spare part data management information system design that was tested by experts and declared valid and the final product was made using the integrated Visual Basic 6 developer software. with MySQL database, and product testing in the field by 3 prospective users has been declared effective.The system developed can overcome problems in the old system at HSC Computer Kaliwungu, resulting in a system that can simplify the work process and the process of making reports in the administration section, which in turn can provide improved services in service handling and customer convenience